Cell's Kitchen: Normalization of Foodplaces in Dutch Penal Institutions - Groeneveld, Elisabeth (The prison journal, 2025)
In popular media, carceral food places are often depicted as large communal mess halls, but this does not reflect the diversity of such spaces worldwide. Carceral geography, while exploring prison spaces, seldom examines foodplaces in detail. Using empirical data from 21 Dutch penal institutions, we describe how incarcerated persons experience these spaces. Some elements of carceral foodplaces are normalized, but others, such as the gap between the frequency of self-catering and the need for bricolage, are not. We recommend more collaborative construction to better understand facility repurposing and its underlying motivations.